The Best Evidence for the Prevention and Management of Lower Extremity Deep Venous Thrombosis After Gynecological Malignant Tumor Surgery: A Systematic Review and Network Meta-Analysis - Hu, Jiaqi; Geng, Yidan; Ma, Jingyi; Dong, Xuefan; Fang, Shuqin; Tian, Jianli (Frontiers in Surgery, 2022)
Background: To search and obtain the relevant evidence of prevention and management of lower extremity deep venous thrombosis after gynecological malignant tumor operation, and to summarize the relevant evidence. Methods: We searched JBI evidence summary, up to date, the national comprehensive cancer network of the United States, the guide library of the National Institute of clinical medicine of the United Kingdom, PubMed, the Chinese biomedical literature database, CNKI, Wanfang and other relevant evidence on the prevention and management of deep venous thrombosis in patients with gynecological malignant tumors. It includes clinical practice guidelines, best practice information book, expert consensus, evidence summary, original research, etc. The retrieval time limit is from database establishment to August 20, 2021. Two researchers independently evaluated the literature quality, combined with professional judgment, and extracted the literature that met the standards. Results: Finally, 18 literatures were included, including 8 guidelines, 3 evidence summaries, 4 systematic evaluations, 2 expert consensus and 1 best practice information volume. A total of 26 pieces of best evidence on the prevention and management of postoperative venous thrombosis in gynecological malignant tumors were summarized. It includes risk assessment, drug prevention, mechanical prevention, management strategy and health education. Conclusion: This study summarized the best evidence of risk, prevention and health management of deep venous thrombosis in postoperative patients with gynecological malignant tumors, so as to provide evidence-based basis for clinical nurses and improve nursing level.